Factors Influencing Accounting Students’ Interest in Pursuing a Career as an Internal Auditor - Hustianto Sudarwadi; Anglin Devita Risqiyawati; Marlina Malino (Advances in Economics & Financial Studies, 2026)
Purpose: This study aims to analyze the relationship between financial compensation, labor market considerations, work environment, professional training, social values, and the interest of accounting students at the University of Papua in pursuing a career as an internal auditor. Research Method: The study used a quantitative cross-sectional survey of 163 college students selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. Results and Discussion: Labor market considerations and professional training are positively and significantly associated with career interest. Financial rewards, work environment, and social values show a positive trend, but the statistical evidence is not yet sufficient. The findings are interpreted as statistical associations, not causality. Implications: The program needs to strengthen its labor market information, audit training, internships, and practitioner involvement. Future research should improve construct validity and expand the sample size. Originality: The study provides contextual evidence regarding the career attributes associated with the interest of students at the University of Papua in the internal auditor profession.